Text Mining Approach to Emotion Analysis in Translation of Surah Yusuf With NRC Emotion Lexicon - Syafiqah, Annisa; Zaman, Syahiduz; Imamudin, Mochamad (UIR PRESS, 2025)
In the digital era, the accessibility of vast textual data, including the Quran, has facilitated broader comprehension of its teachings. This study analyzes the emotions in the English translation of Surah Yusuf using the NRC Emotion Lexicon. The findings show that trust is the most dominant emotion (22.89%), followed by joy (15.66%), anticipation (13.25%), sadness (12.05%), fear (10.84%), anger (9.64%), surprise (8.43%), and disgust (7.23%). These results confirm the text's diverse emotional expressions and the effectiveness of the lexicon-based method. The research aligns with the initial goals and highlights the potential of emotion analysis in understanding religious texts. Future research can expand the analysis to more verses and use machine learning for improved accuracy. This study aids scholars and students in exploring the Quran's emotional and spiritual dimensions and can be adapted to other texts for broader applications.